What is better for sampling canopy spiders in the Amazon rainforest: a good tree or a good canopy? - Carvalho, Leonardo S.; Costa, Érika L. S.; Lo-Man-Hung, Nancy F.; Candiani, David F.; Rodrigues, Bruno V. B.; Dias, Sidclay C.; Bonaldo, Alexandre B. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Despite being one of the largest Neotropical biomes, the Amazon rainforest presents a strong sampling bias. Most of its known spider fauna is reported from easily accessed environments, while canopy spider fauna is understudied. Sampling canopy spider fauna using fogging machines is based on two distinct approaches: (1) sampling the canopy of a target tree species (‘single species’); or (2) sampling the fauna from a closed canopy, with overlapping branches of different tree species (‘closed canopy’). These approaches have never been compared before. In the present manuscript, we provided evidence that fogging samples in both approaches yield a similar number of adult spiders and species. However, species composition is differs between the two methods. The pros and cons of each approach are discussed and the choice between them should depend on project goals.